Isorhamnetin Inhibits Human Gallbladder Cancer Cell Proliferation and Metastasis via PI3K/AKT Signaling Pathway Inactivation - Zhai, Tianyu; Zhang, Xiaoyu; Hei, Zhenyu; Jin, Longyang; Han, Chao; Ko, Audrey Tsznam; Yu, Xiaofeng; Wang, Jiandong (Frontiers in Pharmacology, 2021)
Gallbladder cancer (GBC) is the most common biliary tract tumor with a poor prognosis. Isorhamnetin is a flavonoid compound extracted from Hippophae rhamnoides L. and has several pharmacological effects including anti-inflammatory and anti-cancer properties. We treated GBC-SD and NOZ of GBC cell lines with different isorhamnetin concentrations in vitro. Cell counting Kit-8 (CCK-8) assay, transwell assay, Hoechst 33342 stain assay, flow cytometric analysis, and the colony-forming assay were performed to investigate the effect of isorhamnetin on the proliferation, apoptosis, metastasis and cycle arrest of GBC cells. The western blotting assay was conducted to explore the related protein expression level of GBC cells. The mice xenograft model and immunohistochemistry staining were employed to assess the effect of isorhamnetin in vivo. Isorhamnetin was found to suppress cell proliferation and metastasis, trigger apoptosis and arrest of G2/M phase in GBC cells via the inactivation of PI3K/AKT signaling cascade. Our findings are of clinical significance in providing a novel treatment approach for GBC.